Services: marketing,operations, and management - Jauhari, Vinnie (Oxford University Press, 2010)
Services: marketing,operations, and management / Jauhari, Vinnie. -- New Delhi: Oxford University Press, 2010 658.8 J41 No. of Copies : 1